Massive hemothorax following administration of intrapleural streptokinase - Chai, Feng Yih; Kuan, Yeh Chunn (2011)
The administration of intrapleural streptokinase (IPSK) is widely practiced in the management of loculated empyema thoracis. To our knowledge, there have been only 4 cases of hemorrhagic complications attributed to the administration of IPSK reported in the literature. In this article, we report a case of a 17-year-old girl who received IPSK and developed shock, anemia, coagulopathy and massive hemothorax. Our discussion focuses on the hemorrhagic complication of chest tube insertion and the role of IPSK in blood clot lysis and inhibition of local hemostasis.